Conceptualization of the ‘School’ in the English Available Lexicon of Spanish Adolescents - Jiménez Catalán, Rosa María; Montero-SaizAja, Alejandra (Miscelánea: A Journal of English and American Studies, 2020)
This study explores the conceptualization of ‘School’ in the English lexicon of EFL learners, and compares this lexicon to the meanings attributed to the entry School in English dictionaries. Our first objective aimed at identifying the most frequent content words retrieved by Spanish EFL learners in response to the cue-word SCHOOL in a lexical availability/association task, and comparing them with the meanings attributed by dictionaries. Our second objective aimed at ascertaining whether there were gender similarities or differences in the lexical production and the actual words retrieved by males and females. The quantitative analyses applied to the data revealed a common structure in male and female EFL learners’ available lexicon as well as a high correspondence to the meanings attributed to School in dictionaries. However, the qualitative analysis also uncovered typical patterns related to adolescent school life not present in dictionaries as well as vocabulary not shared by males and females but exclusively generated either by males or by females.
Keywords: Conceptualization; Archetype; Available lexicon; Lexical retrieval; Adolescent EFL learners